A-to-I RNA editing in human disease - Nishikura, Kazuko (Henry Stewart Talks, 2013)
What is A-to-I RNA editing?, Human diseases caused by ADAR1 deficiency, Human diseases caused by ADAR2 deficiency, Human diseases of 5-HT2CR mRNA editing, Human pathological conditions caused by deficiency in microRNA editing